Reducing strategic uncertainty increases group protection in collective risk social dilemmas - Ivo Steimanis; Natalie Struwe; Julian Benda; Esther Blanco (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2025)
Interrelated global crises - climate change, pandemics, loss of ecosystem services and biodiversity - pose risks that demand collective solutions. Uncertainty about others' behavior, coupled with the dependence on some to take collective efforts to mitigate risks for all (e.g. conservation of natural habitats by those living at wildlife boarders to reduce risk of zoonoses), complicates collective action. We extend the experimental collective risk social dilemma to consider that some individuals ('beneficiaries') cannot protect themselves and must rely on others ('providers') for collective protection. Our approach allows to disentangle the relevance of self-interest and uncertainty over the actions of others in explaining self-reliance by providers. Our findings show that reducing strategic uncertainty leads to more collective solutions, with more beneficiaries protected, less resources wasted, and lower inequality. Moreover, we show that institutions inspired by payments for ecosystem services that allow beneficiaries to make compensation transfers to providers of protection are highly effective in fostering collective solutions. Indeed, these voluntary institutions are similarly effective in alleviating the social dilemma as (the hypothetical case of) fully removing strategic uncertainty. Thus, we show that understanding the reasons for self-reliance in collective risk social dilemmas can help develop better institutions to enhance the use of collective solutions, and thereby enhancing social welfare.
Keywords: D70; H41; C92; D64; Q54; 330; Collective risk social dilemma; cooperation; mitigation; adaptation; strategic uncertainty; selfinterest; public good; donation; laboratory experiment